An improved simulation model of switched reluctance motor including transient core losses for steady-state operation. Issue 1 (7th January 2019) - Yan, Wenju; Chen, Hao; Xu, Tong; Wang, Kai
Abstract : Purpose: An improved simulation model of switched reluctance motor (SRM) for steady-state operation that considers the core losses in the stator and rotor is established to obtain the steady performance of the high-speed SRM during the design, analysis and control of SRM driving system more accurately. Design/methodology/approach: The transient core loss model for the material and SRM is presented. Then a new method for calculating the flux density of the motor in real time is introduced, and a steady-state simulation model of the SRM including real-time transient core losses calculation model is established according to the transient flux density. Because the transient core losses calculated by above method are the total core losses of the motor, a core losses distribution method is proposed and the steady-state simulation model of the SRM including the distributed core losses' effect on the phase winding is established. Findings: The comparison results show that the proposed model has higher accuracy than the traditional model, excluding core losses, especially at the moments when phase voltage is turn-on and turn-off. The proportion of the core losses to the motor losses increases with the increase in speed. So, the core losses' effect on the steady-state performance of the high-speed SRM cannot be ignored. Originality/value: The method to obtain flux density in the real time is presented and the improved steady-state simulation model of SRM that considering transient core losses is proposed.